METHODOLOGY OF DESIGNING E-LEARNING COURSES FOR THE PROFESSIONAL (VOCATIONAL) EDUCATION SYSTEM IN WAR AND POST-WAR TIMES - Zuieva, Alona (Professional Pedagogics, 2022)
Relevance: modern conditions of educational activity have made distance and blended learning more relevant; most of the teaching staff of vocational education institutions have chosen the Google Classroom platform and the Google Meet video conferencing tool to support the educational process, but there is no single methodology for designing e-learning courses using these digital tools.Aim: determination of the main components and stages of the methodology of designing e-learning courses for vocational education.Methods: analysis – to determine the state of development of the problem; generalization – for formulating conclusions regarding the main components and stages of the methodology of designing e-learning courses for vocational education.Results: it was established that 84.4% of teachers of vocational education institutions conducted classes and assigned tasks using the Google Classroom platform, and 74.5% of those surveyed chose Google Meet for organizing video conferences. The methodology of designing e-learning courses for blended learning in the system of professional (vocational) education in the war and post-war times is based on the digital tools of the Google Workspace for Education environment, since they are used by the majority of pedagogical workers of vocational education institutions. These tools are easy to use, adaptable, take into account different conditions and technical capabilities of participants in the educational process, and allow taking into account the individual characteristics and educational needs of students.Ukrainian teachers and scientists distinguished from four to eight stages of designing e-learning courses, and determined the different functional content of these stages. The methodology for designing e-learning courses for blended learning has five main stages (ADDIE: Analyzing, Designing, Developing, Implementing, Evaluating), expanded and adapted for the needs of blended learning in vocational education institutions in war and post-war times.Conclusions: The methodology of designing e-learning courses for blended learning in the system of professional (vocational) education in war and post-war times is defined as a set of interconnected methods, forms and means of developing an e-learning course in the Google Workspace for Education environment. It has five main stages of ADDIE design, taking into account the pedagogical processes required for blended learning in vocational education institutions in war and post-war times.This technique makes it possible to develop a clear algorithm of interaction between teachers and students, organization and support of pedagogical processes in an e-learning course, taking into account the peculiarities of the educational process and individual characteristics of students.
Keywords: blended learning; e-learning course; professional (vocational) education; methodology of designing e-learning courses